1982
DOI: 10.1002/1097-0142(19820101)49:1<61::aid-cncr2820490114>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The viability of cells in the waste products of CO2-laser evaporation of cloudman mouse melanomas

Abstract: The viability of cells present in waste products originating during CO2-laser evaporation of Cloudman S91 mouse melanomas was investigated. Cytologic smears showed mainly carbonized particles and thermally damaged cells but some morphologically intact cells as well. Viability was tested with the trypan blue test, by in vitro culture and intramuscular and intraperitoneal inoculations in syngeneic mice. No dye-excluding cells were found in the trypan blue test. Growth was noted neither in vitro nor in vivo in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…Three main mechanisms are in operation to varying degrees: cavitation, heat generation, and protein denaturation [9,12]. The process of cavitation arises from the creation, expansion, and implosion of cavities in liquids [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main mechanisms are in operation to varying degrees: cavitation, heat generation, and protein denaturation [9,12]. The process of cavitation arises from the creation, expansion, and implosion of cavities in liquids [7].…”
Section: Discussionmentioning
confidence: 99%
“…The heat generated by the UAS is a result of internal tissue friction caused by the high-frequency vibrations. In addition, coagulation is achieved partly by denaturing proteins through mechanical disruption of tertiary hydrogen bonds [12].…”
Section: Discussionmentioning
confidence: 99%
“…This issue is of concern because of the potential for viable aerosolized cancer cells to seed distant sites such as trocar incisions leading to port-site metastases through a method known as the chimney effect. Although some studies have failed to show the presence of aerosolized cells in the peritoneal cavity during routine laparoscopic surgery [32], others have demonstrated the presence of cell-sized fragments [33], morphologically intact but nonviable cells [34], and viable cells in surgical smoke [26,35,36]. A 1999 study in which a more sensitive method of cell viability detection was used, a tetrazolium mitochondrial viability assay instead of the tryphan blue assay used in previous studies definitively showed the presence of viable cells in laser and electrocautery smoke [37].…”
Section: Viable Cellsmentioning
confidence: 99%
“…Thirty-two plume samples were obtained from 1984;MacLachlan, 1983; between 21 and 30 years of age; 5 were between 31 and [Alberti, 1981;B e h a et 1981Daniel17 1983, 17 female patients. Of the patients studied, 10 were l984; Hoye, 1967;Mihashi et al, 1974Mihashi et al, , 1986Oosterhuis et al, 1982;Ossoff 40 [Bellina et al, 1981[Bellina et al, , 1982Accepted for publication April 17, 1987. Hoye7 1967terhuis et al, 1982;Voorhies et al, 19841. of procedure, the type of disease, the amount of lasing Dunwoody Road, Atlanta, GA 30342.…”
Section: Introductionmentioning
confidence: 99%